Storytelling and Narrative Legacy: Violence and the Moral Decline of Jaime Deza in Javier Marías’s Tu rostro mañana - Greenhalgh, Matthew C. (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2023)
Javier Marías combined historiography and fiction to examine the consequences of violence in Tu rostro mañana, published in three volumes: Fiebre y lanza (2002), Baile y sueño (2004), and Veneno y sombra y adiós (2007). This interpretation examines the moral decline of Jaime Deza, the narrator-protagonist, in what he sees and the stories he hears to contextualize how Marías combined history with fiction to present nuanced representations of violence. Marías envisioned violence through Deza, who searches for a usable past to navigate the dilemmas he faces in the present.